Performance-Based Framework to Prioritize Adaptive Reuse Gallery Design: A Case Study of Tate Modern Towards Architectural and Cultural Engagement along London Riverfront - Hanapi, Nur Amalina; Morrison, Tessa; Yusof, Hanita (International Journal of Sustainable Construction Engineering and Technology, 2022)
This topic of adaptive reuse of an historical and industrial building of Tate Modern, an art gallery from its previous function as old power station in London. Critical number of research has been done of the industrial buildings which incorporate the adaptive reuses concept on the impact on the universal building practice and economy. But, there has been a minimal extended research with regards to how adaptive reuse building portrays a significant impact to riverfront development planning for the vicinity. Therefore, this paper explores method of the architectural modifications made by both architects involved and its current ramification of cultural network establishment to both sides of the north and south bank of London. As an outcome, these findings adaptive reuse suggest space revivification, construction waste reduction and urban sustainability that promote a new label urban sprawl significance that support the tourism, industry, social and civic engagement for the Thames riverfront development based on the historical building preservation.